Early development of the glass frogs Hyalinobatrachium fleischmanni and Espadarana callistomma (Anura: Centrolenidae) from cleavage to tadpole hatching - Salazar-Nicholls, María-José; Salazar-Nicholls, María-José; E. M. del Pino,; E. M. del Pino, (Amphibian & Reptile Conservation, 2015)
We report the characteristics of embryonic development from cleavage to tadpole hatching in two species of glass frogs, Hyalinobatrachium fleischmanni and Espadarana callistomma (Anura: Centrolenidae). This analysis of embryonic development in centrolenid frogs enhances comparative studies of frog early development and contributes baseline information for the conservation and management of Ecuadorian frogs. These frogs reproduced in captivity and their embryos were fixed for developmental analysis. The morphology of embryos was evaluated in whole mounts, bisections, thick sections, and fluorescent staining of cell nuclei. Egg clutches contained an average of 23 and 35 eggs for H. fleischmanni and E. callistomma, respectively. The eggs of both frogs measured approximately 2.1 mm in diameter. The eggs of H. fleischmanni were uniformly pale green. In contrast, the animal hemisphere of E. callistomma eggs was dark brown and the vegetal hemisphere was light brown. The developmental time of H. fleischmanni and E. callistomma under laboratory conditions was 6 and 12 days, respectively from the 32–cell stage until tadpole hatching. Differences in environmental conditions may be associated with the time differences of early development observed in these frogs. The development of glass frogs from egg deposition to tadpole hatching was staged into 25 standard stages according to the generalized table of frog development. Archenteron elongation began in the early gastrula and notochord elongation began in mid to late gastrula, as in X. laevis. Development of the gastrocoel roof plate (grp) was precocious in the two centrolenid frogs. The grp was detected in the late gastrula of both species; whereas the grp was detected in neurula stages of X. laevis. The presence of the grp in embryos of these frogs suggests that the mechanisms of left-right asymmetry, found in X. laevis and other amphibians, may be shared by these centrolenid frogs. The development of H. fleischmanni and E. callistomma resembles the pattern found in frogs with rapid development such as the aquatic eggs of X. laevis and the development in floating foam-nests in the genus Engystomops (Leptodactylidae). Differences in egg pigmentation were particularly significant in connection with the divergent reproductive strategies of these glass frogs.
Centro Jambatu - ID 1541